Study of some morphological indicators of the obesity component of the Algerian youth soccer - قميني حفيظ (sports creativity, 2025)
This research focused on studying certain morphological indicators of obesity among young football players in Algerian clubs. This was achieved by diagnosing and determining the levels of these obesity indicators. The research sample consisted of youth players with an average age of 13.52 ± 0.53 years, playing for professional teams in the first and second divisions. The study primarily employed a descriptive-comparative approach to identify differences among the players based on their level of athletic practice, playing style, and chronological age. The results showed acceptable values ​​for obesity indicators compared to their counterparts from other Arab and foreign countries (G. Cazorla, 2006). Furthermore, statistically significant differences were observed among different players based on age and level of athletic practice, a finding previously confirmed in similar studies (W. F. Helsen, 2005).